PELAKSANAAN EKSEKUSI PUTUSAN ARBITRASE SIAC DI INDONESIA TERKAIT SENGKETA PENGGUNAAN BAHASA DALAM KONTRAK - Christine Elizabeth (Faculty of Law - Tarumanagara University, 2021)
In the process of organizing an international business contract, the parties involved have the freedom to discuss the essence of said contract, which will then be agreed together. English, as the language known as lingua franca, is often used in conducting an international business contract. Not only language used in the contract, choice of law and choice of forum are also important elements to be included in an international business contract as an anticipative move to face the conflicts that might or might not happen in the future. Arbitration is business people’s popular choice nowadays as the forum to settle their conflicts, because it is thought to be more effective and efficient compared to the conventional solution (litigation). The parties who already agreed to the arbitration clause included in the contract should then follow the procedures. Nonetheless, reality—more often than not—doesn’t fulfill the expectation, just like what happened in the case between Blutether Limited v. PT. MNC Skyvision Tbk. How could such a thing happen? Writer did an extensive research on this case using the normative law research method. Results show that rules regarding the usage of foreign language along with the absence of good faith and fairness in conducting the international business contract played a vital role in the failure of achieving justice in that case. Some changes need to be made regarding those points to support international business contracts with foreign parties.